Etienne and Beverly Wenger-Trayner (2020). Learning to Make a Difference. Value Creation in Social Learning Spaces, Cambridge University Press, ix + 279 pages - Anders Buch (Nordic Journal of Working Life Studies, 2021)
In their work, in their leisure time – yes, indeed in all walks of life – people interact with one another, have new experiences, come to know new things, and learn new things about their environment and the world they inhabit. But how? Philosophers, psychologists, sociologists, anthropologists, cognitive scientists, and many more have theorized this fundamental question and developed theories of learning. Thirty years ago, anthropology professor Jean Lave and cognitive scientist Etienne Wenger developed a social theory of learning that conceptualize learning as a process of situated cognition – legitimate peripheral participation – in communities of practice (Lave & Wenger 1991). This theory – and specifically the concept of communities of practice (CoP) that Etienne Wenger later explored in more detail (Wenger 1998) – have become an influential theoretical and analytical inspiration for researchers in education, organization studies, sociology, social-psychology, and the entire range of disciplines that are preoccupied with the study of social life and working life. (.....)